Association between GeneXpert Diagnosis and Same-Day Initiation of Tuberculosis Treatment in Rural Eastern Uganda - Izudi, Jonathan; Tamwesigire, Imelda K.; Bajunirwe, Francis (The American journal of tropical medicine and hygiene, 2020)
Diagnosis of tuberculosis with GeneXpert and same-day initiation of tuberculosis treatment (SITT) has important public health and clinical benefits. GeneXpert allows for rapid diagnosis, hence presenting an opportunity for SITT.Wedetermined the association between GeneXpert diagnosis and SITT, and the effect of SITT on treatment success rate among adult persons with bacteriologically confirmed pulmonary tuberculosis (BC-PTB) in rural eastern Uganda. We conducted a retrospective cohort study using routinely collected data at 10 health facilities, used modified Poisson regression analysis to determine the association between GeneXpert and SITT, and expressed the results as risk ratio (RR). We used propensity score-matched analysis to match SITT participants to delayed initiation of treatment (DIT) participants and then performed logistic regression analysis to determine the independent effect of SITT on treatment success rate, expressed as odds ratio (OR). Of 1,045 participants, 764 (73.1%) had SITT. The use of GeneXpert for diagnosis of tuberculosis was associated with higher likelihood of SITT (adjusted RR [aRR], 1.28; 95% CI: 1.19–1.37) and for persons with new BC-PTB diagnosis (aRR, 1.16; 95%CI: 1.02–1.32). We successfully matched 530 participants (265 in SITT and 265 in DIT) through 1:1 nearest neighbor caliper matching. Before propensity score-matched analysis, SITT was not significantly associated with treatment success rate (adjusted OR, 0.97; 95% CI: 0.70–1.33). After propensity score matched analysis, SITT remained non-significantly associated with treatment success rate (OR, 0.96; 95% CI: 0.67–1.40). GeneXpert thus increases the likelihood of SITT, but SITT has no significant effect on treatment success rate.
Keywords: Association; GeneXpert Diagnosis; Same-Day Initiation of Tuberculosis Treatment; Rural; Eastern; Uganda; Pulmonary tuberculosis (BC-PTB)